2005
DOI: 10.1186/bcr1336
|View full text |Cite
|
Sign up to set email alerts
|

Mutation analysis of FANCD2, BRIP1/BACH1, LMO4 and SFN in familial breast cancer

Abstract: Introduction Mutations in known predisposition genes account for only about a third of all multiple-case breast cancer families. We hypothesized that germline mutations in FANCD2, BRIP1/ BACH1, LMO4 and SFN may account for some of the unexplained multiple-case breast cancer families.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
34
2
4

Year Published

2006
2006
2018
2018

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 49 publications
(40 citation statements)
references
References 40 publications
0
34
2
4
Order By: Relevance
“…A nonsense mutation 2392C>T (R798X) accounted for the majority of mutations in this gene. These findings have not, however, been replicated in more recent studies [11][12][13][14][15][16][17][18][19].…”
Section: Pharoah Et Al Estimated the Absolute Risk Of Breast Cancer Bcontrasting
confidence: 43%
“…A nonsense mutation 2392C>T (R798X) accounted for the majority of mutations in this gene. These findings have not, however, been replicated in more recent studies [11][12][13][14][15][16][17][18][19].…”
Section: Pharoah Et Al Estimated the Absolute Risk Of Breast Cancer Bcontrasting
confidence: 43%
“…SFn can be combined with a variety of proteins, including signal protein kinase, phosphorylase and transmembrane receptors, and plays an important role in the regulation of the cell cycle and cell apoptosis (14). in recent years, the function of SFN (14-3-3σ) in tumors has been reported, but with varying results in different epithelial tumors.…”
Section: Discussionmentioning
confidence: 99%
“…Several subsequent studies screened the BRIP1 coding sequence in large numbers of BRCA1/2 negative familial breast cancer families from populations in Northern Europe (Luo et al, 2002;Karppinen et al, 2003;Vahteristo et al, 2006), North America (Rutter et al, 2003) and Australia (Lewis et al, 2005). This resulted in the detection of one frameshift mutation and several missense mutations, none of which segregated with breast cancer in the families.…”
Section: Breast Cancermentioning
confidence: 99%
“…The authors concluded that FA gene mutations, other than in BRCA2, are unlikely to make a significant contribution to the risk of familial breast cancer. The FANCD2 gene was screened for mutations in an Australian cohort of 30 non-BRCA1/2 familial breast cancer families, but no pathogenic mutations were detected (Lewis et al, 2005). An association study of seven SNPs in the FANCA, FANCL and FANCD2 genes was carried out to determine whether any of these SNPs conferred susceptibility to breast cancer in the Spanish population (Barroso et al, 2006).…”
Section: Breast Cancermentioning
confidence: 99%